Disiplin yang Diberikan Orangtua Berdasarkan Kolose 3:12-16 dalam Pembentukan Karakter Anak - Renny Maria; Agustinus Manullang (Institut Agama Kristen Negeri Manado, 2022)
This study aims to describe the discipline given by parents based on Colossians 3:12-16 in the formation of children's character in Christian families. This research is a descriptive qualitative research with a literature study method, namely by using books, journals, and articles as the main source. The results of this study indicate that parents must use love as a form of discipline and parents should educate with patience and gentleness and parents must educate by beating and reprimanding according to God's word so that children will respect their parents more, become gentle and patient individuals and have integrity.